Design of a fixed-bed column with vegetal biomass and its recycling for cr (VI) Treatment (2022)
The aim of this work is to design a fixed-bed column with vegetal biomass of Eichhornia crassipes and the process of recycling it for treatment via the adsorption of water loaded with chromium (VI). In the first stage, the relationship between the fixed-bed density and the microparticle density is calculated, giving a model for the design of the fixed bed. Using this model, two systems for the treatment of Cr (VI)-contaminated water were designed and built. The vegetable biomass at three particle diameters of 0.212 mm, 0.30 mm and 0.45 mm was evaluated in the removal of Cr (VI) from water using the designed fixed-bed systems, giving the best removal of Cr (VI) with the lowest size particles and allowing the validation of the proposed model with the Thomas model. The incorporation of iron into the biomass allowed for the treatment of near 2.0 L of polluted solution, removing around 90% of Cr (VI), while it was only possible to treat nearly 1.5 L when using raw biomass, removing around 80% of Cr (VI). The recycling of the biomass was achieved via the elution of Cr (VI) with EDTA, permitting the reuse of the material for more than five treatment cycles.